Metabolic traits of sediment bacteria in karst caves in the light of environmental changes - Mulec, Janez; Pašić, Lejla; Oarga-Mulec, Andreea (Frontiers in Microbiology, 2025)
IntroductionKarst subterranean systems are vulnerable ecosystems that have not yet been studied adequately at the microbial functional level. Cave sediments deposited over different time periods host diverse microbial communities that play a critical role in nutrient cycling and pollutant degradation.MethodsIn this study, we investigated microbial diversity and metabolic capacity in recently deposited alluvial sediments and an ancient palaeo-river deposit in a karst cave system. Using 16S rRNA gene amplicon metagenomic analysis, community-level physiological profiling (CLPP), and chemical characteristics of the environment, the influence of key environmental factors on microbial community composition and substrate degradation, concentrating particularly upon sediment age, oxygen availability, and temperature, was assessed.ResultsThe results showed different microbiome compositions and metabolic characteristics between sites. The old alluvial sediment exhibited low taxonomic and functional diversity, accompanied by elevated heavy-metal concentrations, suggesting that sediment age might act as a geochemical filter, limiting microbial function. In contrast, a periodically flooded site showed high metabolic versatility and taxonomic diversity, emphasizing the ecological role of hydrological pulses in maintaining functional microbial diversity. CLPP metrics linked community structure to functional potential, revealing adaptive traits in key taxa such as Polaromonas, Methylibium, and Beggiatoa.DiscussionThese results demonstrated the value of integrating functional and taxonomic approaches in subsurface environments and provide insights into microbial resilience, biogeochemical processes, and the potential for applied environmental use.